ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN DI SD NEGERI 36 PALEMBANG - Riska Amelia; Sukardi; Nugroho Nad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify students' learning difficulties in mathematics on addition and subtraction material in elementary school. The method used by the researcher is a qualitative descriptive method. The data sources in this study are test results, student and teacher interview results, and documentation results taken in class. The data analysis techniques used are data collection, data reduction, data presentation, and conclusions or data verification. The results of this study show that the forms of mathematics learning difficulties experienced by students consist of several components, namely difficulties in reading, difficulties in determining learning media, difficulties in writing, and difficulties in memorizing and remembering formulas. The factors causing mathematics learning difficulties originate from a lack of student interest in mathematics learning, poor student memory, many students still experiencing difficulties in reading and writing, an unconducive classroom atmosphere, and a lack of parental guidance at home.